On the taxonomic position of the genera Krundia, Breukoscelis, and Uphodato (Hemiptera, Auchenorrhyncha, Fulgoroidea) described from the Insect Limestone of the Isle of Wight - Gnezdilov, Vladimir M.; Emeljanov, Alexandr F. (Zootaxa, 2020)
Three fossil genera, Krundia Szwedo, 2019, Breukoscelis Szwedo, 2019, and Uphodato Szwedo, 2019, described in the family Issidae are transferred to other families according to the shape and venation of forewings. Krundia Szwedo is transferred to the family Tropiduchidae. Breukoscelis Szwedo is placed in synonymy under Uphodato Szwedo and transferred to the family Cixiidae. Forewing venation of the members of Issidae, Tropiduchidae, and Cixiidae are discussed and illustrated.